Nature and the environment in pre-Columbian American life - Kowtko, Stacy (The Greenwood Press "Daily life through history" series, 2006)
Prehistoric North Americans lived on, in, and surrounded by nature. As a result, everything they were resulted from this co-existence. From interpersonal relations to supernatural beliefs, from housing size and function to the food they ate and clothing they wore, the life of Native Americans before the arrival of Europeans was intimately intertwined with the environment. What is known about these societies is often sketchy at best, having survived largely through archaeological remains and oral tradition. Scholars have tried to understand Native American history on its own terms, trying to understand who and what they were in reality - a complex, diverse multitude of populations that defined themselves entirely through what they saw, heard, and experienced everyday - their natural environment. Nature and the Environment in Pre-Columbian American Life provides an overview of all aspects of how native peoples interacted with the environment.